Synthesis, Structural, Spectroscopic, and Hirshfeld Surface Analysis, and DFT Investigation of Benzaldehyde Semicarbazone. (16th June 2022) - Sudha, N.; Anbuselvi, S.; Jyothula, Sudhakar; Thiruppathi, A.; Vijayakumar, B.; Parmar, Kartikeya; Puthilibai, G.; Kumar, Leevesh
Abstract : By using slow evaporation, single crystals of BDSC (chemical name: 2-benzylidenehydrazine carboxamide) have been formed. A slow evaporation approach was used to generate BDSC single crystals. By using single-crystal XRD, the nonlinear characteristics of the material were studied. The presence of molecular groups was carefully examined using fundamental vibrational analysis. A Hirshfeld analysis was used to study the interactions between molecules. A series of UV-visible, photoluminescence, and VCD spectroscopic experiments were used to verify the optical characteristics of the material. In order to determine the electrical characteristics, dielectric investigations were carried out. Tests of Vickers hardness were used to measure mechanical strength. The SHG behaviour of the crystal was determined using the Kurtz–Perry method. To assess the molecule's thermal stability, all quantitative calculations were performed using the B3LYP approach with a basis function of 6-31 + G(d, p) and TG/DTA experiments.